Philippines : Staff Report for the 2005 Article IV Consultation and Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the 2005 Article IV Consultation on the Philippines highlights managing short-term vulnerabilities and higher investment and growth. Power generation tariffs have been raised to substantially cut the losses of the National Power Corporation (NPC). A risk to the near-term outlook for the Philippine economy is that political events, such as possible constitutional change, serve to sideline economic reforms. Executive Directors agreed that rebalancing the composition of public expenditure, with reduced current outlays providing space for capital and social spending, should form an integral part of the fiscal consolidation.